Probabilistic Assessments of Safety Instrumented Function by Considering the Justification of Cost-benefit Using ALARP Evaluation Method - Amornsak Potiteerabuit; Teerawat Thepmanee (My University, 2015)
This paper addresses the conceptual design step that probabilistic calculations are done to show that any given design meets the performance requirements of the Safety Instrumented Function(SIF) by considering the justification of cost-benefit. The average Probability of Failure on Demand (PFD avg ) of the one out of one (1oo1) sensing device was calculated by simplified Markov model. The effects of the imperfect proof test and proof test interval on the value of PFD avg were then studied. As the test cost occurs during device proof test, high frequently of testing along the device life cycle increases the cost while decreases the PFD avg value and risk of the sensing device. In this work, the relationship between the risk reduction achieved and the investment cost was investigated in detail using As Low As Reasonably Practicable (ALARP) method. Based on the ALARP analysis, the optimized interval of proof test was then evaluated.
Keywords: Software Reliability and Analysis Research